CRIMINAL LAW REFORMS IN RECENT TIMES: ISSUES AND CHALLENGES - Malik, Neeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Criminal law is basically a fundamental part of the judiciary system, which protects society and upholds justice. The main purpose of this law is to maintain social order and rehabilitate offenders. Ensures to protection of the rights of individuals and maintains rules regarding illegal and legal behaviour. In India criminal law protects citizens and improves overall justice delivery. The new criminal laws especially emphasize the human rights of the citizens and provide effective outcomes for victims. The modification and introduction directly contribute towards reducing the crime rate and ensuring India’s justice system becomes more robust and simple. The importance of reforms and changes in the proper legislation process highlighted the fact that the existing laws are specially backdated. A certain colonial Era is directly reflected in the Justice system. Several old laws in the section have become irrelevant and undoubtedly delay the overall justice system. However, there is a certain concern which can reflect the criminal law reforms in India. Misuse of power by certain authorities and inappropriate implementation can cause severe consequences. The criminal law has been amended many times which enables a legal framework to maintain societal changes and emerging challenges along with technology advancement. When the criminal justice system came to deliver justice by mitigating delay and compliance it created a fair justice system for communities and people. The idea of reform of criminal law mainly emphasizes victim empowerment, modernized evidence rule and many more. Also, certain areas needed to be addressed such as accountability, transfer, privacy, freedom of speech, the potential for abuse and interpretation and implementation challenges. Recent significant criminal law reforms in India here will be discussed and challenges or issues will be identified properly. Bharatiya Nyaya Sanhita (BNS) replaced the Indian penal code (IPC) and mostly aimed to influence the severity of punishment and criminal offences. Bharatiya Nagarik Suraksha Sanhita (BNSS) is a modified version of the Code of Criminal Procedure (CrPC) which focuses on victim protection and streamlining investigations. The Latest version of the Indian Evidence Act is Bharatiya Sakshya Adhiniyam (BSA) which incorporates forensic advancements and digital evidence. Those laws have been implemented with several challenges and issues but they also foster the judiciary system of India. These new laws effectively prioritize victims’ rights and developed Updater support mechanisms for them also simplify the legal processes by reducing delays.